Symbols Reflected in Behind A Mask Or A Woman Power by Alcott - Indra, Indra; Syamsurrijal (Jurnal Ilmu Sosial dan Humaniora, 2024)
Behind a Mask Or A Woman's Power by Louisa May Alcott is a novell that tells the story of Jean Muir, a governess who is both cunning and mysterious. Jean manipulates the members of the wealthy Coventry family to secure her position and achieve her personal goals. Through charm and deceit, she reveals her strength and resilience, challenge the conventional roles of women in society. The novel explores themes of power, identity, and societal expectations, shows the complexities of female agency in the 19th century. the main character reveals her true character through subtle manipulations gradually. She captivates each family member in different ways such as winning over Gerald, the eldest son, with her charm, gaining the admiration of Bella, the youngest daughter, and intriguing Sir John, the family patriarch. Each character sees a different side of Jean, tailored to their vulnerabilities and desires. This is a descriptive qualitative research. The data source are taken from a novel titled Behind A Mask Or A Woman’s Power by Louisa May Alcott. The primary data are dialogues, quotations, conversations and narrations from each character which represent symbols in the novel. The concept of symbol by Pierce is used to analysis symbols in the novel. In Peirce's semiotic theory, symbols are signs that represent objects through a conventional or arbitrary relationship. A symbol is a type of sign that relies on a learned or agreed upon connection between the and the signified. Unlike icons or indexes, symbols do not have a direct resemblance or causal link to their objects. The research problem are what are symbols appeared in the novel ? what do symbols mean in the novel ? the result of the research find out several symbols such as mask, blue, dog, face, chair, dark, sweetheart . The mask serves as a means for the character to conceal her true self, while the dog serves as a distraction from her confusion when interacting with others. The sweetheart represents an intimate and desire, the dark suggests strange things and perilous situations, and the face announces his appearance to convey his reaction.